Źródła konkurencyjnej przewagi polskiego agrobiznesu na rynkach Unii Europejskiej - Drelichowski, Ludosław (Polish Agribusiness Competitive Advantage at the European Union Markets, 2005)
The significance of up-to-date knowledge management solutions in enterprises undertaking an activity on the EU markets is described. One can made analysis of factors determining a success in export of foodstuffs to the EU markets. Stability of analyzed determinants let present very optimistic forecasts of growth of surplus in domestic food trade between 2005-2007.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 160-165